2016
DOI: 10.1097/psy.0000000000000352
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine and Tryptophan Levels in Patients With Schizophrenia and Elevated Antigliadin Immunoglobulin G Antibodies

Abstract: Objective Several studies have reported an association between non-celiac gluten sensitivity and schizophrenia. Immune and kynurenine pathways have also been implicated in the pathophysiology of schizophrenia, and certain proinflammatory immune mediators may increase kynurenine (KYN) and reduce tryptophan (TRP) levels. Methods We thus measured serum anti-gliadin IgG, KYN and TRP in 950 patients with schizophrenia. Patients with antibody level at the 90th percentile or higher of control participants (21.9% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 53 publications
(57 reference statements)
1
13
0
Order By: Relevance
“…Consistent with some previous studies, the KYN/TRP ratio was also increased in the plasma of individuals with SCZ in our study, and an elevated KYN/ TRP ratio is associated with immune activation in individuals with SCZ. 40,41 In the brain, immune activation can activate astrocytes, where KYN can be transaminated to KYNA through KYN aminotransferases (KATs). 42,43 Thus, we speculate that elevated plasma KYNA levels and KYN/TRP ratio may indicate higher KYNA levels in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with some previous studies, the KYN/TRP ratio was also increased in the plasma of individuals with SCZ in our study, and an elevated KYN/ TRP ratio is associated with immune activation in individuals with SCZ. 40,41 In the brain, immune activation can activate astrocytes, where KYN can be transaminated to KYNA through KYN aminotransferases (KATs). 42,43 Thus, we speculate that elevated plasma KYNA levels and KYN/TRP ratio may indicate higher KYNA levels in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…In the mentioned study, schizophrenic patients with elevated anti-gliadin IgG had increased serum kynurenine levels and kynurenine to tryptophan ratio compared with patients without increased anti-gliadin IgG. Tryptophan to kynurenine conversion is linked with inflammation and raised cortisol levels [ 67 ]. Another study found that anti-casein IgG antibodies are linked with type I bipolar disorder, psychotic symptoms and mania severity [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, increased plasma IgA responses measured here may have a mucosal origin related to gut permeability (Roomruangwong et al, 2017a). Previous work, in both pregnant and non-pregnant women, shows that IgA responses to TRYCATs were significantly and positively related to IgA/IgM responses to antigens and LPS of gram-negative commensal bacteria (Roomruangwong et al, 2017a), whilst it is known that gut-derived inflammation following gluten sensitivity (as measured with anti-gliadin IgG autoantibodies) could contribute to TRYCAT pathway activation (as measured with the kynurenine/tryptophan ratio) in schizophrenia (Okusaga et al, 2016). It is also of note that alterations in gut microbiota and permeability are associated with changes in the activity of a number of brain regions, including the amygdala (Fernandez-Real et al, 2015), which is a brain nuclei that is classically linked to mood/affective regulation, including in schizophrenia (Anderson, 2011).…”
Section: Discussionmentioning
confidence: 99%